Flipped Classroom Learning Model through STEM Approach to Improve the Ability of Mathematical Creative Thinking - Ardiansyah, Misfalla Roudlo Putri; Waluya, St. Budi; Dwijanto, Dwijanto (Universitas Negeri Semarang, 2024)
In recent years, there has been a growing interest in innovative teaching methodologies to improve student engagement and learning outcomes. The integration of the flipped classroom model with the STEM approach has shown promising potential in fostering critical and creative thinking skills among students. This study aims to find out whether the flipped classroom learning model through the STEM approach can be used to enhance students' creative thinking skills in the subject matter of a three-variable linear equation system for Grade X at MA Mathalibul Huda Mlonggo in the 2022/2023 academic year. The method used in this study is an experimental method with a one-group pretest-posttest experimental design. The research results found that the flipped classroom learning model through the STEM approach was able to improve students' mathematical creative thinking abilities in the material of a system of three-variable linear equations. This can be seen from the T-test result, which obtained the results so that sig.(2-tailed) <α=0,05. Therefore, it can be concluded that the flipped classroom learning model with the STEM approach is able to improve students' mathematical creative thinking skills in the subject matter of a three variables linear equation system for Grade X at MA Mathalibul Huda Mlonggo for the 2022/2023 academic year. This is also reinforced by the results of the normalized gain test which has a value of 0,39, indicating a moderate category of improvement. Hence, it can be concluded that the flipped classroom learning model through the STEM approach is able to improve students' mathematical creative thinking skills in the subject matter of the three-variable linear equation system Grade X at MA Mathalibul Huda Mlonggo in the 2022/2023 academic year.